3p+8=6-9p+3

Simple and best practice solution for 3p+8=6-9p+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3p+8=6-9p+3 equation:


Simplifying
3p + 8 = 6 + -9p + 3

Reorder the terms:
8 + 3p = 6 + -9p + 3

Reorder the terms:
8 + 3p = 6 + 3 + -9p

Combine like terms: 6 + 3 = 9
8 + 3p = 9 + -9p

Solving
8 + 3p = 9 + -9p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '9p' to each side of the equation.
8 + 3p + 9p = 9 + -9p + 9p

Combine like terms: 3p + 9p = 12p
8 + 12p = 9 + -9p + 9p

Combine like terms: -9p + 9p = 0
8 + 12p = 9 + 0
8 + 12p = 9

Add '-8' to each side of the equation.
8 + -8 + 12p = 9 + -8

Combine like terms: 8 + -8 = 0
0 + 12p = 9 + -8
12p = 9 + -8

Combine like terms: 9 + -8 = 1
12p = 1

Divide each side by '12'.
p = 0.08333333333

Simplifying
p = 0.08333333333

See similar equations:

| 1/2(100-x)=40 | | z=ln(x^2+y^2+4*x-2*y+1) | | 1p+2p=18 | | 12p=5p+28 | | y^-3/2=125 | | 2x-10x=x-10 | | 4x-8=7x-35 | | x^2+x-12=(x-a)(x-b) | | s/8=4.25 | | 5+2sinx-7=0 | | 9x^2-12x-41=0 | | V=AO | | (3x)/(e^(0.5X^2)) | | y=4E+07x | | -4y/-6 | | y=4E+07x-20026 | | a-(9b-13b)= | | 3+5n=35 | | -7x-10=59 | | 25t=30(t+10) | | 2j+18=32 | | 8z+4(5z+10)=0 | | 3y+9=2y-5 | | s/12=21/2 | | -7+40y=35y-6 | | n^2+1n-13=0 | | 17+13x=165 | | 2ln(x+2.8)=3.2 | | -4/5 | | 5-3x+7x=-39 | | 2(9s+4)-8=2(5s+3)-8 | | 4n-10n+35=1.2 |

Equations solver categories